Temperature post out-of-hospital cardiac arrest: the TOPCAT study. (26th December 2010) - Lyon, Richard
Abstract : Introduction: Out-of-hospital cardiac arrest (OHCA) is a significant cause of death and severe neurological disability. The only postreturn of spontaneous circulation (ROSC) therapy shown to increase survival is mild therapeutic hypothermia (MTH). The relationship between body temperature post OHCA and outcome is still poorly defined. Methods: Prospective observational study of all OHCA patients admitted to a single centre for a 14-month period. Oesophageal temperature was measured in the Emergency Department and Intensive Care Unit (ICU). Select patients had prehospital temperature monitoring. Results: 164 OHCA patients were included in the study. 105 (64.0%) were pronounced dead in the Emergency Department. 59 (36.0%) were admitted to ICU for cooling; 40 (24.4%) died in ICU and 19 (11.6%) survived to hospital discharge. Patients who achieved ROSC and had oesophageal temperature measured prehospital (n=29) had a mean prehospital temperature of 33.9°C (95% CI 33.2 to 34.5). All patients arriving in the ED post OHCA had a relatively low oesophageal temperature (34.3°C, 95% CI 34.1 to 34.6). Patients surviving to hospital discharge were warmer on admission to ICU than patients who died in hospital (35.7°C vs 34.3°C, p<0.05). Patients surviving to hospital discharge also took longer to reach target MTH temperature than non-survivors (2 h 48 min vs 1 h 32 min, p<0.05). There was no difference in mean arterial blood pressure on arrival in the ED between survivors and non-survivors. Conclusions: Following OHCA all patients have oesophageal temperatures below normal in the prehospital phase and on arrival in the Emergency Department. This questions the need for prehospital cooling post-OHCA patients. Patients who achieve ROSC following OHCA and survive to hospital discharge are warmer on arrival in ICU and take longer to reach target MTH temperatures compared to patients who die in hospital. The mechanisms of action underlying oesophageal temperature and survival from OHCA remain unclear and further research is warranted to clarify this relationship.